Adjudication and Enforcement of Spousal Maintenance After Divorce within Indonesian Religious Courts - Apri Yahya Langago; Weny Almoravid Dungga; Nurul Fazri Elfikry (Legtimacy: Journal of Law and Islamic Law, 2026)
This study examines the determination of wives' post-divorce maintenance rights from the perspective of the Gorontalo District Religious Court, focusing on Case No. 539/Pdt.G/2024/PA.Gtlo. It addresses two core issues: the factors influencing judicial decisions on maintenance awards and the effectiveness of enforcement mechanisms. Employing an empirical juridical methodology with content analysis and basic jurimetrics, the research identifies four primary determinants: husband's financial capacity (60% weighting), marital circumstances, wife's nusyuz status, and actual needs aligned with Gorontalo's Living Wage Standard. Judges apply substantive justice principles under Islamic Law Compilation (KHI) Article 149 and Supreme Court Circular No. 5/2021, setting iddah maintenance at 25-40% of husband's income. However, enforcement effectiveness remains low at 30%, hampered by defendants' lack of seizable assets, limited court staff (two clerks for 1,200 annual cases), and informal compromise culture. The study proposes a tripartite Maintenance Enforcement Task Force, integrated SIPP-PA digital asset database, and community legal literacy programs to achieve 70% compliance per RPJMN 2025-2029 targets, shifting family justice from reactive adjudication to proactive enforcement.